Fatty acid deficiency signs predict the severity of reading and related difficulties in dyslexic children. - Richardson, A; Calvin, C; Clisby, C; Schoenheimer, DR; Montgomery, P; Hall, J; Hebb, G; Westwood, E; Talcott, J; Stein, J (2000)
It has been proposed that developmental dyslexia may be associated with relative deficiencies in certain highly unsaturated fatty acids (HUFA). In children with attention-deficit/hyperactivity disorder, minor physical signs of fatty acid deficiency have been shown to correlate with blood biochemical measures of HUFA deficiency. These clinical signs of fatty acid deficiency were therefore examined in 97 dyslexic children in relation to reading and related skills, and possible sex differences were explored. Children with high fatty acid deficiency ratings showed poorer reading (P<0.02) and lower general ability (P<0.04) than children with few such clinical signs. Within males (n=72) these relationships were stronger, and fatty acid deficiency signs were also associated with poorer spelling and auditory working memory (P<0.05, P<0.005 respectively). Within females (n=25) no associations were significant. These results support the hypothesis that fatty acid deficiency may contribute to the severity of dyslexic problems, although sex differences merit further investigation.